Analisis Kualitas Auditor, Leverage Dan Persentase Saham Initial Public Offering Terhadap Earnings Management Perusahaan Go Public - Hasanuddin Hasanuddin (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2019)
AbstractThe action of corporate management to intervene in the process of drafting financial statements is an act of dysfunctional behavior that will affect the enhancement of personal welfare management and The company's employees and the value of its leadership. This research aims to test and prove empirically the cause and influence of earnings management in the company that go public after the enactment of Accounting and Auditing Enforcement Release (AAER) by Security Exchange Commission (SEC). The variables tested were reputation Auditor, Leverage and stock percentage of Initial Public Offering (IPO) at the company that go Public on the Indonesia Stock Exchange from 2000 to 2004. The method of analysis used is multiple regression that previously done testing through several stages. Results show that the leverage variable significantly affects earnings management. This indicates that the debt that is the source of external funds used to finance the business continuity is strongly associated with earnings management.